Cultivo de peixes em tanques-rede : efeito sobre a energia e a estrutura trófica em ambientes aquáticos. - Figueroa Eche, Lourdes Mercedes (2008)
The aim of this study was to identify the fish cage culture effect on the caloric and isotopic content in fishes. The experiment was carried out in two tributaries of Rosana's reservoir: Corvo and Guairacá. The results of this dissertation are show in two chapters. In the first chapter the objective was to identify the effect of fish cage culture on the quantity of energy present in the muscle and the general well-being of Auchenipterus ostemystax. Just females individuals were selected with resting gonadal maturation stage and standard lenght between 17-19cm. Caloric density was determinated in a calorimeter bumb Parr 1261. Significants differences were found in caloric density and condition factor of A. osteomystax among the months of the experiment for both rivers. The highest values were identified at the end of the experiment. There was a significant correlation (p < 0.005) among the caloric density and the condition factor during the experimental period. In the second chapter were determined variations at the C-13 and N-15 of the aquatic food web of Corvo river. For these, isotopic compositions of muscles fishes belonging to different trophic categories: Auchenipterus osteomystax (insectivore), Satanoperca pappaterra (invertivore), Plagioscion squamosissimus (piscivore) and the raising fish Oreochromis niloticus (omnivore); the invertebrate Corbicula fluminea (filterer), sediment, particulate organic carbon (COP) and ration fish food were investigated. It was verified increase in the C-13 values in muscles of all fish species out of the net-cages and the invertebrate C. fluminea. Furthermore, was found depletion in the C-13 values in the muscle of O. niloticus at the end of the experiment. However, significant differences were not found among the isotopic values of C-13 of the COP and sediment. C. fluminea, A. osteomystax and O. niloticus showed more negative N-15 values among the beginning and the end of the experiment. However, the N-15 values of S. pappaterra, P. squamosissimus and the sediment did not differ significantly. In summary, the present dissertation showed that the fish cage cultures installation can to promote shifts in the species trophic conditions, increasing the general well-being and the somatic energy allocation. As a result of this, it can to promotes changes in the isotopic composition of aquatic food web organisms, which have an effect over the ecology of the native species, and consequently for the ecosystem.